A feasibility study on the establishment of an institutional archive in preservation of Fe Del Mundo Medical Center's history - Sio, Kendrik Philipp S. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
This study evaluated the feasibility of establishing an institutional archive in Fe Del Mundo Medical Center (FDMMC) based on the factors of market, technical, and financial feasibility.